Classifying Raman spectra of extracellular vesicles based on convolutional neural networks for prostate cancer detection. (7th November 2019) - Lee, Wooje; Lenferink, Aufried T.M.; Otto, Cees; Offerhaus, Herman L.
Abstract: Since early 2000s, machine learning algorithms have been widely used in many research and industrial fields, most prominently in computer vison. Lately, many fields of study have tried to use these automated methods, and there are several reports from the field of spectroscopy. In this study, we demonstrate a classification model based on machine learning to classify Raman spectra. We obtained Raman spectra from extracellular vesicles (EVs) to find tumor derived EVs. The convolutional neural network (CNN) was trained on preprocessed Raman data and raw Raman data. We compare the result from CNN with results from principal component analysis that is widely used among in spectroscopy. The new model classifies EVs with an accuracy of >90%. Moreover, the new model based on CNN is also suitable for classifying the raw Raman data directly without preprocessing with a minimum accuracy of 93%. Abstract : In this study, we demonstrate a classification model based on machine learning to classify Raman spectra. We obtained Raman spectra from EVs to discriminate tumor derived EVs from blood product derived EVs. The CNN was trained on preprocessed Raman data and raw Raman data. We compare the result from CNN with results from PCA.